Design and Development of a Web-Based Certificate Application Information System in Patamawai Village - Hinggu Maramba Nau, Mahir; Yogia Pradana Uly, Hawu; Hariadi, Fajar (Cattleya Darmaya Fortuna, 2024)
The certificate service at the Patamawai Village Office is currently not computerized or integrated, so it is inefficient. The certificate service's inefficiency causes village residents to visit the village office several times if documents or requirements still need to be completed. Another obstacle is that people must wait quite a long time when the Village Head is away from the office; they have to wait for village staff for quite a long time. Many village residents are also processing different certificates, and many certificates are scattered and even lost. This research aims to create an information system for submitting certificates in Patamawai Village to make it easier for the community to process certificates as one solution to this problem. Three types of certificate services are provided in this information system: Certificate of Incapacity, Certificate of Business, and Certificate of Traditional Marriage. This research was conducted in Patamawai Village, Mahu District, East Sumba Regency, from May to July 2024. This information system was built using the Waterfall method because the information system is made more structured. The information system was created using the Hypertext Preprocessor programming language, while the user interface was created using Balsamiq Mockups. The data collection techniques were observation, interviews, documentation, and questionnaires. This information system was tested using black-box testing and SUS testing. The black box testing results show that all test results correspond to the expected results in each scenario. Thus, the black box test results have a success percentage of 100%. These results show that the certificate information system runs smoothly. The certificate information system that has been created has an average SUS score of 84.3, so it is categorized as a grade of A based on the SUS test. Thus, the information system for submitting certificates in Patamawai Village is ready to be used by residents and staff to facilitate the processing of certificates in the village.